2019
DOI: 10.1016/j.annemergmed.2019.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Effectiveness of Nasal Compression With Tranexamic Acid Compared With Simple Nasal Compression and Merocel Packing: A Randomized Controlled Trial

Abstract: Study objective: The primary objective of this study is to compare the effectiveness of 3 treatment protocols to stop anterior epistaxis: classic compression, nasal packing, and local application of tranexamic acid. It also aims to determine the frequency of rebleeding after each of these protocols.Methods: This single-center, prospective, randomized controlled study was conducted with patients who had spontaneous anterior epistaxis. The study compared the effect of 3 treatment options, tranexamic acid with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…Vaiman et al 10 included patients with epistaxis due to any cause while in the remaining RCTs only patients with primary spontaneous epistaxis were eligible for inclusion. Two studies excluded patients on anticoagulation therapy (although not antiplatelet) 19,20 . A study by Mathiasen et al 22 excluded patients with international normalised ratio (INR) over 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaiman et al 10 included patients with epistaxis due to any cause while in the remaining RCTs only patients with primary spontaneous epistaxis were eligible for inclusion. Two studies excluded patients on anticoagulation therapy (although not antiplatelet) 19,20 . A study by Mathiasen et al 22 excluded patients with international normalised ratio (INR) over 4.…”
Section: Resultsmentioning
confidence: 99%
“…Four RCTs with a total of 269 patients were eligible for inclusion and meta-analysis (Table 3). 10,[19][20][21] Two studies compared FLOSEAL ® with nasal packs, 20,21 only patients with primary spontaneous epistaxis were eligible for inclusion. Two studies excluded patients on anticoagulation therapy (although not antiplatelet).…”
Section: Randomised Controlled Trialsmentioning
confidence: 99%
“…TXA is also used for idiopathic epistaxis in inpatients or outpatients visiting the emergency department, especially in patients taking antithrombotic drugs. Moderate evidence has shown that topical TXA significantly reduced the duration of epistaxis and the risk of rebleeding (within 10 days) compared to nasal packing [16][17][18]. For the treatment of epistaxis, TXA can be applied via TXA-soaked cotton pledgets or sprayed, followed by external compression for 15 min (Table 1) [16][17][18].…”
Section: Bleeding Disordersmentioning
confidence: 99%
“…Donald Jeanmonod, Guhan Rammohan and Rebecca Jeanmonod* Department of Emergency Medicine, St. Luke's University Hospital, Bethlehem, PA, USA *Address all correspondence to: rebeccajeanmonod@yahoo.com an atomizer and/or saturating nasal tampons with topical application of 500 mg of the IV formulation (TXA 100 mg/ml). Care must be taken in patients with higher risk of systemic thrombosis as systemic absorption may be variable when TXA is applied to the nasal mucosa [63].…”
Section: Author Detailsmentioning
confidence: 99%